Establishing an Antimicrobial Stewardship Program in Sierra Leone: A Report of the Experience of a Low-Income Country in West Africa - Sulaiman Lakoh; Mohamed Bawoh; Hannah Lewis; Ishmael Jalloh; Catherine Thomas; Shuwary Barlatt; Abdulai Jalloh; Gibrilla F. Deen; James B. W. Russell; Mustapha S. Kabba; Moses N. P. Batema; Cecily Borgstein; et al. (MDPI AG, 2023)
Antimicrobial Resistance (AMR) is a growing global health challenge that threatens to undo gains in human and animal health. Prevention and control of AMR requires functional antimicrobial stewardship (AMS) program, which is complex and often difficult to implement in low- and middle-income countries. We aimed to describe the processes of establishing and implementing an AMS program at Connaught Hospital in Sierra Leone. The project involved the setting up of an AMS program, capacity building and performing a global point prevalence survey (GPPS) at Sierra Leone's national referral hospital. Connaught Hospital established a multidisciplinary AMS subcommittee in 2021 to provide AMS services such as awareness campaigns, education and training and review of guidelines. We performed a GPPS on 175 patients, of whom more than half (98, 56.0%) were prescribed an antibiotic: 63 (69.2%) in the surgical wards and 53 (51.2%) in the medical wards. Ceftriaxone (60, 34.3%) and metronidazole (53, 30.3%) were the most common antibiotics prescribed to patients. In conclusion, it is feasible to establish and implement an AMS program in low-income countries, where most hospitalized patients were prescribed an antibiotic.